A Survey of the Application of Grounded Theory Methods for Understanding Aspects of Design Subject in Architectural Education; the Case of ‘Eivan’ - Elham Bakhtiari Manesh (صفه)
The present research studies the use of Grounded Theory methods in architectural education. The question here is whether the application of these methods can improve students’ comprehension of the design subject. The study is based on analysing an exercise based on these methods and focused on the ‘eivan’. It pursues an applied objective using a descriptive analytical method. It starts with analysing contents of the literature extracting their relevant aspects, and then moves on to present and analyse an exercise designed to use Grounded Theories methods. A comparison is then made between students’ initial perceptions about the eivan with their post-exercise perceptions to measure potentials of the application of Grounded Theories in architectural education. The results show that this method help students expand, correct and make accurate their perceptions, thereby approaching more key aspects of the subjects.